Parallel processing in the brain's visual form system: an fMRI study - Shigihara, Yoshihito; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
We here extend and complement our earlier time-based, magneto-encephalographic (MEG), study of the processing of forms by the visual brain (Shigihara and Zeki, 2013) with a functional magnetic resonance imaging (fMRI) study, in order to better localize the activity produced in early visual areas when subjects view simple geometric stimuli of increasing perceptual complexity (lines, angles, rhomboids) constituted from the same elements (lines). Our results show that all three categories of form activate all three visual areas with which we were principally concerned (V1, V2, V3), with angles producing the strongest and rhomboids the weakest activity in all three. The difference between the activity produced by angles and rhomboids was significant, that between lines and rhomboids was trend significant while that between lines and angles was not. Taken together with our earlier MEG results, the present ones suggest that a parallel strategy is used in processing forms, in addition to the well-documented hierarchical strategy.